Performance optimization of a gas turbine-based cogeneration system - Yilmaz, T (IOP PUBLISHING LTD, 2006)
In this paper an exergy optimization has been carried out for a cogeneration plant consisting of a gas turbine, which is operated in a Brayton cycle, and a heat recovery steam generator (HRSG). In the analysis, objective functions of the total produced exergy and exergy efficiency have been defined as functions of the design parameters of the gas turbine and the HRSG. An equivalent temperature is defined as a new approach to model the exergy rate of heat transfer from the HRSG. The optimum design parameters of the cogeneration cycle at maximum exergy are determined and the effects of these parameters on exergetic performance are investigated. Some practical mathematical relations are also derived to find the optimum values of the adiabatic temperature ratio for given extreme temperatures and consumer temperature.
Keywords: EFFICIENCY; Physics